2002
DOI: 10.1007/s11661-002-0339-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-propagating reaction induced by ball milling in a mixture of Cu2O and Al powders

Abstract: The mechanochemical reduction of Cu 2 O with Al was induced via ball milling. A self-propagating reaction took place in two distinctly different ways. If the mass of the reactant powder mixture was large enough, ignition happened within a few seconds after starting the mill. Neither the activation of the reactants nor the formation of a powder layer covering the surfaces of the milling tools were necessary. If the mass of the charge is smaller than a critical value, the self-propagating reaction is ignited onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…This method can be combined with a solid-state reaction [6]. Processing of aluminum matrix nanocomposites by mechanically driven reduction of metal oxides with aluminum has been frequently studied [7][8][9][10][11][12][13][14][15][16][17][18][19]. Fine dispersions can also be produced by a reaction between the powder particles and milling atmosphere during the course of milling.…”
Section: Introductionmentioning
confidence: 99%
“…This method can be combined with a solid-state reaction [6]. Processing of aluminum matrix nanocomposites by mechanically driven reduction of metal oxides with aluminum has been frequently studied [7][8][9][10][11][12][13][14][15][16][17][18][19]. Fine dispersions can also be produced by a reaction between the powder particles and milling atmosphere during the course of milling.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggestible that, the reaction between the substances at the high temperature (>840 • C) occurs abruptly with a high reaction rate which can be accompanied by melting of product copper [15]. Under this condition, the higher interfacial energy of Al 2 O 3 /solid-Al compared with Al 2 O 3 /liquid-Al serves as a driving force for "particle pushing" [16]. In other words, the alumina particles are pushed into the liquid aluminum to form agglomerates.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports are available in open literature on the fabrication of Al-Al 2 O 3 nanocomposites through the reaction between Al melt and CuO; for instance, Kobashi and Choh [10] have studied the in-situ process and shown that the formed alumina particles were fine, but the macroscopic distribution was not uni- form; Chen and Sun [11] have examined the in-situ synthesis of Al 2 O 3 /Al-Cu composite by initiating the reaction in compact of mixed Al and CuO powders in molten aluminum; Hoseini and Meratian [12] have fabricated a Al-Al 2 O 3 composite by reduction of copper oxide via melting and casting aluminum through a squeeze casting system. Synthesis of Al based nanocomposites by mechanically induced solid-state reaction has recently been examined by some researchers, e.g., Wu and Li [13] have synthesized nanostructured aluminum matrix composite reinforced with CuAl 2 (100-500 nm in size), Al 2 O 3 and Al 4 C 3 (10-50 nm in size); Shengqi et al [14] have investigated the mechanical driven reduction reaction of CuO and Al powder; the solid reactions between CuO and Cu-14 at.%Al alloy or Cu 9 Al 4 inermetallic compound during high energy mechanical milling have been studied by Ying and Zhang [15]; the self-propagating reaction between CuO and Al by mechanical milling was demonstrated by Bakhshai et al [16]. It is known that when the enthalpy of the reaction is sufficiently high ( H = −1209 kJ/mol Al 2 O 3 in Al-CuO system [4]) and a critical milling energy is applied, the self-propagation combustion reaction can be ignited during synthesizing.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these disadvantages, metallothermic reduction of the tungsten oxide during milling has been proposed with magnesium [15] and aluminum [16] as reducing agents. Mechanochemical method was also applied to prepare the Cu powder by milling the copper oxides with Mg [17] or Al [18]. The feasibility of carbothermal reduction during milling was separately investigated in the Cu 2 O-C [19] and WO 3 -C [20] binary systems.…”
Section: Introductionmentioning
confidence: 99%